Influence of digital economy on youth unemployment in West Africa. Issue 1 (2nd January 2021) - Azu, Nnanna P.; Jelivov, Gylych; Aras, Osman Nuri; Isik, Abdurrahman
Abstract: The world has progressively become a global village and most economic activities in today's world embrace digitisation. Digitisation is gradually being appreciated in West Africa but its impact on youth unemployment is relatively unknown. Thus, this study aims at filling this research gap by measuring digitisation in two perspectives; internet penetration rate and mobile telephone subscription. The Im-Pesaran-Shin (IPS) unit-root test affirms that the data are suitable for panel ARDL estimation technique. The estimation establishes that youth unemployment, digitisation and the control variables are cointegrated. This study also reveals that digitisation could reduce youth unemployment in West Africa, both at the short-and long-run but not convincing due to low appreciation of digital technologies. In the short-run, the result is consistent in some countries but not same and robust in some others. Thus, the paper concludes that increasing digitisation would enhance employment opportunities for the youths in the West African region.